Identification of a Pyruvate-to-Lactate Signature in Pancreatic Intraductal Papillary Mucinous Neoplasms - Penheiter, Alan R. (Pancreatology, 2017)
OBJECTIVE: We used transcriptomic profiling and immunohistochemistry (IHC) to search for a functional imaging strategy to resolve common problems with morphological imaging of cystic neoplasms and benign cystic lesions of the pancreas. METHODS: Resected pancreatic cancer (n = 21) and normal pancreas were laser-capture micro-dissected, and transcripts were quantified by RNAseq. Functional imaging targets were validated at the protein level by IHC on a pancreatic adenocarcinoma tissue microarray and a newly created tissue microarray of resected intraductal papillary mucinous neoplasms (IPMNs) and IPMN-associated adenocarcinomas. RESULTS: Genes encoding proteins responsible for cellular import of pyruvate, export of lactate, and conversion of pyruvate to lactate were highly upregulated in pancreatic adenocarcinoma compared to normal pancreas. Strong expression of MCT4 and LDHA was observed by IHC in >90% of adenocarcinoma specimens. In IPMNs, the pyruvate-to-lactate signature was significantly elevated in high grade dysplasia (HGD) and IPMN-associated adenocarcinoma. Additionally, cores containing HGD and/or adenocarcinoma exhibited a higher number of peri-lesional stromal cells and a significant increase in peri-lesional stromal cell staining of LDHA and MCT4. Interestingly, the pyruvate-to-lactate signature was significantly upregulated in cores containing only low grade dysplasia (LGD) from patients with histologically confirmed IPMN-associated adenocarcinoma versus LGD cores from patients with non-invasive IPMNs. CONCLUSION: Our results suggest prospective studies with hyperpolarized [1-(13)C]-pyruvate magnetic resonance spectroscopic imaging are warranted. If these IHC results translate to functional imaging findings, a positive pyruvate-to-lactate imaging signature might be a risk factor for invasion that would warrant resection of IPMNs in the absence of other worrisome features.